BUYING AND DISTRIBUTION ANALYSIS OF GOODS FOR KITCHEN BY THE PURCHASHING PART (Case Study at Kuta Central Park Hotel) - Kadek Agustina (Politeknik Negeri Bali, 2019)
This study aims to determine the application of goods and distribution purchases for kitchen by purchasing department at Kuta Central Park Hotel. Data was collected by interview, observation, and documentation with the help of note-taking techniques. Furthermore, the data was analyzed by qualitative descriptive analysis method. The results showed that the purchase of goods for the kitchen at Central Park Kuta Hotel uses two ways. First, through the daily market list. Purchasing goods through this process is a type of item that does not last long enough and requires special storage areas, such as: dairy products, meat and poultry, herbs and spice, seafood, vegetables and fruits, ice cream, process meat, pastry and bakery, syrup, juice food, and also groceries. Second, namely through purchase requisition submitted by the storekeeper section for inventory at the general store. The type of goods purchased through this process is a type of groceries that can last more than one year. The flow of goods distribution from the general store to the kitchen starts with using the form store requisition made by the kitchen, then submitted to the storekeeper. The storekeeper issues the item in accordance with the request and a copy of the form is given to the kitchen staff who receive the item for review.